DESIGN AND OPTIMIZATION OF AN AUTOMATED MODULAR SYSTEM FOR DISTRIBUTION, MOVEMENT AND STORAGE OF GOODS - Kernagis, Marius; Vaičiulytė, Ingrida (PROFESSIONAL STUDIES: Theory And Practice, 2022)
The automation of various processes, the development of technological potential and the ongoing fourth industrial revolution lead companies to digitize and automate business processes. In order to adapt to the fourth industrial revolution, Šiauliai State College representatives, together with the engineering staff of the companies, have taken the initiative in this area. During the implementation of INOSTART projects, automation processes were design, adapted for warehouses and helping workers to transport heavy loads. A logistics system has been created, which integrates a mobile logistics robot using image detection cameras and distance measuring laser systems, as well as optimized system performance. Keywords: automation, logistic terminal, prototyping, robots, optimization.